Bacterial degradation of 3,4,5-trimethoxycinnamic acid with production of methanol. - Donnelly, M I (1981)
When grown on 3,4,5-trimethoxycinnamic acid, a strain of Pseudomonas putida oxidized this compound and also 3,4,5-trimethoxybenzoic, 3,5-dimethoxy-4-hydroxybenzoic (syringic), and 3,4-dihydroxy-5-methoxybenzoic (3-O-methylgallic) acids, but 3,5-dimethoxy-4-hydroxycinnamic and other acids bearing structural resemblances to the growth substrate were oxidized only slowly. These results indicate that two carbon atoms of the side chain of 3,4,5-trimethoxycinnamate were released before oxidative demethylation occurred to give the ring-fission substrate, 3-O-methylgallate. Oxidation of 3,4,5-trimethoxycinnamate by intact cells gave equimolar amounts of methanol, which was derived from the methoxyl group of 3-O-methylgallate. The tricarboxylic acids, 4-carboxy-2-keto-3-hexenedioic and 4-carboxy-4-hydroxy-2-ketoadipic acids, were shown to be formed by the action of a cell extract upon 3-O-methylgallate; therefore, methanol was released either during or immediately after fission of the benzene nucleus. Cell extracts, prepared from several independent soil isolates after growth on 3,4,5-trimethoxy derivatives of benzoic, cinnamic, and beta-phenylpropionic acids, rapidly oxidized 3-O-methylgallate without added cofactors. It is concluded that the reactions investigated serve generally as a source of methanol in nature.